FePS3 electrodes in all-solid-state lithium secondary batteries using sulfide-based solid electrolytes. (1st July 2017) - Fujii, Yuta; Miura, Akira; Rosero-Navarro, Nataly Carolina; Higuchi, Mikio; Tadanaga, Kiyoharu
Highlights: FePS3 is employed as the electrode in an all-solid-state lithium secondary battery. FePS3 electrode works without the use of solid electrolytes and conductive additives. The discharge capacity of the cell is 107 mAh g −1 at the 30th cycle. FePS3 electrode has lithium ion and electron conducting paths. Graphical abstract: Abstract: In bulk-type all-solid-state lithium batteries with sulfide-based solid electrolytes, composite electrodes, in which an active material, a solid electrolyte, and a conductive additive are mixed, have been used to enhance lithium-ion diffusion and electronic conductivity. However, the addition of electrolytes and electron-conductive additives to the composite electrodes decreases the amount of active materials in the batteries. In the present study, FePS3 was employed as the electrode in an all-solid-state lithium secondary battery, without mixing the solid electrolytes and conductive additives. The all-solid-state cell using the FePS3 electrode exhibited reversible charge-discharge behavior for more than 30 cycles under a constant current density of 0.13 mA cm −2 at room temperature. The discharge capacity of the cell was 107 mAh g −1 at the 30th cycle. This behavior was comparable to that of a cell with an electrode including a solid electrolyte and/or a conductive additive, indicating that the FePS3 electrode had sufficient paths of lithium ions and of electron conduction. These results suggest that FePS3 is an attractive iron-based electrode for an all-solid-state battery using a sulfide-based solid electrolyte.